Expression and effect mechanism of CXCL12 gene in kidney renal clear cell carcinoma: a bioinformatics study - Wei-en CHEN; Qun-xiang REN (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo investigate the expression and effect mechanism of CXCL12 gene in kidney renal clear cell carcinoma. Methods UALCAN database was used to analyze the expression of CXCL12 gene and protein in kidney renal clear cell carcinoma. TCGA database was used to obtain the expression of CXCL12 gene, BMP family gene and clinical information，and Kaplan-Meier was used to analyze the survival curve. The differentially expressed genes in the CXCL12 high/low-expression groups in kidney renal clear cell carcinoma were screened and GO analysis was performed to obtain relevant signaling pathway. ResultsLower expressions of CXCL12 gene and relative protein were found in the tissues of kidney renal clear cell carcinoma. The overall survival rate and disease specific survival rate in the patients with high expression of CXCL12 gene were significantly higher than those in the patients with low CXCL12 gene expression. The majority of the up-regulated genes associated with high CXCL12 gene expression were identified in BMP-related pathway. The expression of CXCL12 is positively correlated with four BMP family genes and significantly higher overall survival rate was observed in the patients with higher expressions of any of the four BMP family genes. ConclusionCXCL12 gene may play an important role in the progression of kidney renal clear cell carcinoma and CXCL12 gene expression is associated with BMP family genes.